The Effect of Financial Performance on Company Value with Sustainability Report Disclosure as an Intervening Variable - Abd Aziz, Marwa; Mukhzarudfa, Mukhzarudfa; Mansur, Fitrini (Journal of Management, Economic, and Financial, 2024)
This study aims to analyze the influence of financial performance on company value by disclosing sustainability reports as an intervening variable in mining sector companies listed on the IDX in 2018-2022. This research population is mining sector companies listed on the IDX by disclosing sustainability reports. The research sample withdrawal technique is by using the purposive sampling method, where samples are selected on the basis of the suitability of sample characteristics with the specified sample selection criteria. Data analysis in this study uses SEM (Structural Equation Modeling) analysis using SmartPLS software version 4. The results of this study show that: 1) Financial Performance has an influence on the disclosure of sustainability reports; 2) Financial performance affects the value of the company; 3) Sustainability reports have an influence on the company's value; 4) Financial performance has no influence on the company's value through sustainability reports